2019
DOI: 10.1108/ijhcqa-06-2018-0156
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the operational risk factors in public hospitals in an Indian state

Abstract: Purpose Risk management in the healthcare sector is a highly relevant sub-domain and a crucial research area from the humanitarian perspective. The purpose of this paper is to focus on the managerial/supply chain risk factors experienced by the government hospitals in an Indian state. The present paper analyzes the inter-relationships among the significant risk factors and ranks those risk factors based on their criticality. Design/methodology/approach The current research focuses on 125 public hospitals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 43 publications
0
13
0
3
Order By: Relevance
“…Other scholars usually cite thresholds, which are usually empirical values, to reduce the workload of the matrix computation. [46][47][48][49] The introduction of such thresholds may bias the structural model, so this study used expert opinion for scoring as the data source.…”
Section: Calculate the Degrees Of Influence And Being Influencedmentioning
confidence: 99%
“…Other scholars usually cite thresholds, which are usually empirical values, to reduce the workload of the matrix computation. [46][47][48][49] The introduction of such thresholds may bias the structural model, so this study used expert opinion for scoring as the data source.…”
Section: Calculate the Degrees Of Influence And Being Influencedmentioning
confidence: 99%
“…, 2013), rural healthcare systems (Kumar 2018), medical tourism (Debata et al. , 2013; Jain and Ajmera, 2018), public hospital risk factors (Vishnu et al. , 2019), among others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Past research has focused on ISM as a methodology to provide greater understanding in a variety of industry sectors including its applications in manufacturing (Meade and Sarkis, 1999;Purohit et al, 2016), logistics and supply chain (Ravi and Shankar, 2005;Singh, 2011), vendor selection (Mandal and Deshmukh, 1994), knowledge management (Singh et al, 2003), information system projects (Hughes et al, 2020), energy conservation (Saxena and Vrat, 1992), risk assessment (Li et al, 2019), humanitarian supply chain initiatives (Bag et al, 2020;Yadav and Barve, 2015), among others. Specific cases of ISM applications in the pharmaceutical and healthcare industry can also be found in existing research: pharmaceutical sales (Wasuja et al, 2012), pharmaceutical returns (Ali, 2017), medical education (Sarikhani et al, 2020), healthcare supply chain (Dixit et al, 2019), healthcare quality (Talib and Rahman, 2015;Vaishnavi and Suresh, 2020), device development Kirkire, 2016, 2017), healthcare waste management (Thakur and Anbanandam, 2016), medical surgery performance (Dev et al, 2013), rural healthcare systems (Kumar 2018), medical tourism (Debata et al, 2013;Jain and Ajmera, 2018), public hospital risk factors (Vishnu et al, 2019), among others. That said, no study was found to have studied contextual barriers to PV.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Esta variante es extremadamente contagiosa dado que se han encontrado a la fecha diversas mutaciones, la más común es delta. Vishnu et al (2019), mencionan que la gestión de riesgos en el sector salud es importante, además de ser un área de investigación crucial desde el punto de vista humano. Tener una adecuada administración de riesgos debe identificar, medir y controlar los riesgos a los que se está expuesto (Capasso et al, 2019).…”
Section: Introductionunclassified